Isolation and characterization of effective microorganism (phosphate solubilizing bacteria) from oil palm rhizhopheric soil and evaluation of their potential to be act as bio fertilizer / Ahmad Solehin Alias - Alias, Ahmad Solehin (Faculty of Plantation and Agrotechnology, 2018)
The methods that are not only efficient, but also have low cost of agricultural input, supplementary, renewable, safe and environmental friendly are now being the priority in agricultural industry. This research is focusing on identifying either with the inoculations of phosphate solubilizing bacteria (PSB) give effects to solubilisation of phosphorus in soil and become available for plant uptake or there is no significance at all. To address this, two treatments are set up which are Merlimau soil with Phosphate Solubilizing Bacteria (PSB) as T1 while Merlimau soil without Phosphate Solubilizing Bacteria as T2. Available P for the treatments and the value of soil pH are being taken for before and after running the research. Other than that, the growth performance of oil palm seedlings was also recorded with the measurement of oil palm seedling height, number of leaves and the width of oil palm seedling leaves on once in four days within two months. The soil analysis for available P and the soil pH was found to have significant increase when treated with PSB as shown for the result of T1. The plant analysis for the growth performance of oil palm seedlings also shows that better growth of plant for the soils that have been treated with PSB. Thus, the application of PSB to the soil can increase the availability of P and reduce the soil acidity. In addition, it gives effect to the performance of the oil palm seedlings growth where this research showed an increased of plant height, larger width of leaves and increase number of leaves compared to the soils that does not treated with PSB. However, to ensure this application of this can produce significant effects, several effective considerations must be taken.